High-titer anti-interferon-γ neutralizing autoantibodies linked to opportunistic infections in patients with adult-onset still's disease - Chen, Po-Ku; Liao, Tsai-Ling; Chang, Shih-Hsin; Yeo, Kai-Jieh; Chou, Chia-Hui; Chen, Der-Yuan (Frontiers in Medicine, 2023)
Objective Neutralizing anti-interferon (IFN)-γ autoantibodies are linked to opportunistic infections (OIs). To explore the association between anti-IFN-γ autoantibodies and OIs in patients with adult-onset Still's disease (AOSD), we aimed to examine the ability of these autoantibodies to blockade signal transducer and activator of transcription (STAT1)-phosphorylation and chemokines production. Methods Serum titers of anti-IFN-γ autoantibodies were quantified using ELISA in 29 AOSD and 22 healthy controls (HC). The detectable autoantibodies were verified with immunoblotting assay, and their neutralizing capacity against IFN-γ-signaling was evaluated with flow-cytometry analysis and immunoblotting. IFN-γ-mediated production of supernatant chemokines, including monocyte chemoattractant protein-1 (MCP-1) and IFN-γ inducible protein-10 (IP-10), were measured by ELISA. Results Among 29 AOSD patients, high titers of anti-IFN-γ neutralizing autoantibodies were detectable in two patients with OIs. Immunoblotting assay revealed more effective inhibition of STAT1-phosphorylation in THP-1 cells treated with sera from autoantibody-positive AOSD patients (56.7 ± 34.79%) compared with those from HC (104.3 ±29.51%), which was also demonstrated in flow-cytometry analysis (47.13 ± 40.99 vs. 97.92 ± 9.48%, p < 0.05). Depleted serum IgG from anti-IFN-γ autoAbs-positive AOSD patients with OIs restored phosphorylated STAT-1 upon IFN-γ treatment. Sera from autoantibody-positive AOSD patients more effectively inhibited IFN-γ-mediated production of MCP-1 (45.65 pg/ml) and IP-10 (22.44 pg/ml) than sera from HC (263.1 pg/ml and 104.0 pg/ml, both p < 0.05). Serum samples showing the strongest inhibition of IFN-γ-signaling were from two patients with high-titer autoantibodies and OIs. Conclusion AOSD patients have a high positive rate and titers of anti-IFN-γ autoantibodies. The remarkable blockade effect of high-titer autoantibodies on IFN-γ-mediated STAT1-phosphorylation and chemokines could make these patients susceptible to OIs.